Pengaruh Likuiditas, Leverage, Profitabilitas, dan Ukuran Perusahaan terhadap Harga Saham : (Studi Empiris pada Perusahaan yang Tergabung dalam Indeks Saham Investor33 di Bursa Efek Indonesia 2019-2023) - Amelia Marta Ningsih; Said Said; Idris Idris (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of liquidity, leverage, profitability, and company size on the share prices of companies that are members of the Investor33 index on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This study uses a quantitative approach with purposive sampling techniques, so that 17 companies out of a total of 46 companies that meet the criteria are obtained. The data used is secondary data in the form of annual financial statements obtained from the IDX's official website. The analysis method used was multiple linear regression with the help of the Statistical Program for Social Science (SPSS) software version 25. The results of the analysis show that the leverage and profitability variables have a significant effect on the stock price, which indicates that the company's capital structure and ability to generate profits are important factors in the investor's assessment. In contrast, the liquidity variables and company size do not show a significant influence on the stock price, which means that the company's ability to meet short-term obligations and operational scale are not the main determinants in the formation of the stock price on the index. These findings provide implications for investors and company management to pay more attention to profitability and leverage aspects in financial strategies and investment decision-making. This research can also be a reference for further studies related to the analysis of financial ratios and capital market dynamics in Indonesia.